Neurofinance: An interdisciplinary Science of correlating the Neurology and the Individual Investment Patterns of Buyers (International Journal of Scientific Research and Management (IJSRM), 2017)
Present article is a conceptual research to document the importance Neurofinance. Researchers have spent a couple of days to understand the concept and approach for the Investment Patterns of Buyers in any sector. This comprises of the data from secondary sources. It has been observed that the Investment Pattern of individuals is based on their reaction and perception. The study identifies that the formal procedures and practices provide a striking substantiation of the brain activity associated with financial decision-making, thus showing the importance of Neurofinance as an effective tool for improved economic decision-making through brain mapping techniques. The findings help towards understanding the risk preferences and the wherewithal while investing. Neurofinance is an interdisciplinary area that attempts to elucidate the human decision-making, the neural activity that shapes the understanding of the brain, the adeptness in processing various alternatives available following a particular course of action.